Um der Sache willen: Karl Barths Schriftauslegung in der kirchlichen Dogmatik - Bergner, Gerhard (Forschungen zur systematischen und ökumenischen Theologie, 2015)
"Exegesis exegesis exegesis and again!" This appeal Karl Barth once adopted in February 1933 by its theology students in Germany - and he has heeded this appeal. In his magnum opus, the Church Dogmatics, there are numerous biblical exegetical digressions, representing not less than the methodological backbone of his dogmatic work according to Barth's own statement. But how can the relationship between exegetical observation and dogmatic theories in the KD accurately describe? The methodology used Barth in his interpretation of the Bible? And what influence does the "doctrine of Scripture" in KD I / 2 on its own interpretation practice in the other volumes of KD from? These are the questions that so far are largely unknown in the Barth-research, Gerhard Bergner goes in depth to provide at the end of the question, in view of current challenges, particularly in light of the "crisis of Protestant scripture principle" to contribute what Barth's exegesis, able